Towards an Ontological Learners’ Modelling Approach for Personalised e-Learning - Hosseini, Seyed Ali; Tawil, Abdel-Rahman H.; Jahankhani, Hossein; Yarandi, Maryam (International Journal of Emerging Technologies in Learning (iJET), 2013)
The rapid advancements in the semantic web technologies has enabled personalised learning based on learnerâ??s characteristics in the learning process. We have implemented a Personalised Adaptive e-Learning system (onto-PAdeL) which uses an ontological approach in design-ing learnersâ?? models. Thus, this paper focuses on describing our approach for modelling learners based on their charac-teristics such as abilities, learning style(s), prior knowledge and preferences. The system uses Item Response Theory (IRT) for calculating learnerâ??s abilities. The learning style can be represented according to different theories, each of which supports personalisation in different ways. We show that using ontologies for learner modelling, in addition to many different benefits, enables reasoning for adaptive learning.